Multifunctional wound dressing for highly efficient treatment of chronic diabetic wounds. Issue 6 (15th September 2022) - Ma, Tengfei; Zhai, Xinyun; Jin, Mengdie; Huang, Yongkang; Zhang, Mengzhen; Pan, Haobo; Zhao, Xiaoli; Du, Yaping
Abstract: As the number of diabetics increases yearly and diabetic ulcer is the most concerned diabetic complication, it is of great urgency to develop a novel multifunctional material with high efficiency to promote diabetic wound healing. In this paper, ceria (CeO2 )‐modified upconversion nanoparticles which loaded in polycaprolactone membranes were successfully prepared as a ceria‐based wound dressing for chronic wound healing. In this system, near‐infrared (NIR) light is used as a switch to control the photodynamic antibacterial therapy by converting the NIR photons into ultraviolet light, which can further trigger CeO2 to produce reactive oxygen species. In addition, the well‐known antioxidant ability of CeO2 endows the wound dressing with prominent capability to resist the oxidative stress around chronic wounds. In summary, both photodynamic antibacterial therapy and good antioxidant property are realized simultaneously in this CeO2 ‐based system to promote the healing of diabetic chronic wounds. Abstract : Ceria modified upconversion nanoparticles which are loaded in polycaprolactone membranes are successfully prepared as a ceria‐based wound dressing for chronic wounds healing. The excellent photodynamic antibacterial property and antioxidant activity endow this ceria‐based wound dressing with outstanding capacity to promote the healing of chronic wounds.